Understanding the Concept of Intellect and Revelation from the Perspectives of Asy'ariyah and Maturidiyah - Hendrawan Hendrawan (Islamic Studies in the World, 2024)
Background. Understanding of Ahlussunnah wa al-Jamaah is a label that is often referred to as the understanding of the users of the sunnah of the prophet more specifically, because it no longer uses pure reason in its actions but uses revelation as its support. Purpose. The purpose of this study is to identify and further examine the differences and similarities between the two main schools in Aswaja, namely Asy'ariyah and Maturidiyah. Method. This study uses a model of qualitative research with the aim of getting what the researcher wants to achieve. In qualitative research it contains elements of research that can produce descriptive data in the form of data or verbally from an object under study, in this study also conduct a review of reference studies in order to ensure and integrate the theory and data written in the presentation of this research. Results. This research found that Ahlussunnah wa al-Jamaah (Aswaja) prioritises revelation as the main guide, in contrast to approaches that rely on pure reason. Asy'ariyah, as the mainstream of Aswaja, has a significant and widespread influence, emphasising the balance between revelation and reason. Maturidiyah, although similar to Ash'ariyah, shows differences in geographical distribution and some theological aspects, but remains in line with Aswaja principles.. Conclusion. This research highlights the relationship between reason and revelation in Ahlussunnah wa al-Jamaah (Aswaja), showing that these two elements have often been the focus of research in human history. Prophet Muhammad, as the bearer of Islam, is recognised as the last prophet who brought modern, up to date and universal teachings. The difference between Al Maturidiyah and Al Assariyah lies in their approach to the creed. The Maturidis emphasise the role of reason in establishing the creed based on Qur'anic verses in a rational and logical manner. In contrast, the Ashariyyah emphasise that in order to know God, shara' must be the primary guide, although they do not neglect the role of reason either.